2015
DOI: 10.4028/www.scientific.net/amm.781.203
|View full text |Cite
|
Sign up to set email alerts
|

Signal Analysis of Scratch-Detection on Magnetic Disc by Using Light Reflection Approach

Abstract: In hard disk manufacturing, a process of quality inspection of magnetic disc is crucially focused on finding traces of scratch that occur on the surface by various sources such as production process, machinery, tribology or recording head. It may affect the efficiency of magnetic disc’s read/write ability. Many approaches have been proposed to detect the scratch by either destructive or non-destructive testing. In this study, it shows an analysis of signals from the detected scratches on the magnetic disc by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Therefore, a new technique of low cost, easy process, and scratch detectability has been presented by using ordinary laser doppler and CD pick-up head to inspect surface details because of its advantages on the measurement of object roughness and the identification of scratch location, in a compromising process [8,9]. Moreover, numerous studies have recently shown interesting results of using DVD pick-up head to detect the reflective DNA layers on a DNA chip slide as its potentiality to show the shape of the DNA and count the number of cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a new technique of low cost, easy process, and scratch detectability has been presented by using ordinary laser doppler and CD pick-up head to inspect surface details because of its advantages on the measurement of object roughness and the identification of scratch location, in a compromising process [8,9]. Moreover, numerous studies have recently shown interesting results of using DVD pick-up head to detect the reflective DNA layers on a DNA chip slide as its potentiality to show the shape of the DNA and count the number of cells [10].…”
Section: Introductionmentioning
confidence: 99%